(3eaGgjegG , eGNdgG , YedjGJgG GdeYGUQIs - (3adGM MSf(B, (3YOGj GdMSjfjs ((3YeGf(B:s (3OGQ hGFd(B,s, 2006)
(3eaGgje h eOGNd GdGSJQGJjLjI h GdGOGQI GdGSJQGJjLjI , YedjGJ GdGOGQI GdGSJQGJjLjI , GdHjFI GdNGQLjI h GdJfGaSjI defXeGJ GdGYeGd , Jbjje GdHjFI GdOGNdjI ddefXeI h GdJMdjd GdGSJQGJjLj h COhGJg GdGSGSjI , GdNjGQGJ h GdHOGFd GdGSJQGJjLjI dhMOGJ GdGYeGd GdGSJQGJjLjI h GdGSJQGJjLjGJ GdhXjajI , YedjGJ GdJfajP GdGSJQGJjLj aj efXeGJ GdGYeGd h YedjGJ GdQbGHI GdGSJQGJjLjI h Jbjje GdGOGA GdGSJQGJjLj , JMdjd GdaLhI GdGSJQGJjLjI , COhGJ JMdjd h CSGdjH bjGS Gdehba GdGSJQGJjLj , GdGOGQI GdGSJQGJjLjI aj GdefXeGJ GdJj dG JgOa Gdi GdQHM h aj GdefXeGJ GdOhdjI(B.s
(3bGFeI GdLOGhd U(B.7 (3; bGFeI GdGTcGd U(B.9s
Keywords: (3GdEOGQI GdYGeIs; (3GdGOGQIs; (3Jbjje GdCOGAs